Antibodies against serotonin have no diagnostic relevance in patients with fibromyalgia syndrome. - Werle, Egon; Fischer, Heinrich P.; Müller, Annette; Fiehn, Walter; Eich, Wolfgang (The journal of rheumatology, 2001)
To determine the prevalence and potential diagnostic relevance of autoantibodies against serotonin, thromboplastin, and ganglioside Gm1 in patients with fibromyalgia syndrome (FM).
Gesehen am 21.01.2022